Meningkatkan Keaktifan Siswa Pembelajaran Pak Model PBL Berbasis Symbolic Way Kelas VII SMP Xaverius 2 Jambi - Andreas Ardhana Prihatmoko (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve student learning outcomes in Catholic Religious Education and Character Education through the application of the Problem Based Learning (PBL) model based on the Symbolic Way. The issue faced is the lack of active student engagement in Catholic Religious Education classes. The method used in this research is Classroom Action Research conducted in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The method believed to be effective in increasing student engagement is the Problem Based Learning (PBL) model based on the Symbolic Way. The PBL model allows students to engage in learning knowledge related to the problem and develop skills to solve it, while the Symbolic Way as a learning medium refers to the use of self-symbols, representations, or visual aids that can help students understand more abstract concepts. The results show that the application of the PBL model based on the Symbolic Way significantly enhances student learning motivation. The average score of students in the implementation of PBL in the first cycle was 80, increasing to 90 in the second cycle. Additionally, observations of student activities indicate an increase in active participation during the learning process. Thus, it can be concluded that the PBL model is effective in enhancing students' active participation.